Clinical and molecular features and therapeutic perspectives of spinal muscular atrophy with respiratory distress type 1. Issue 9 (20th June 2015) - Vanoli, Fiammetta; Rinchetti, Paola; Porro, Francesca; Parente, Valeria; Corti, Stefania
Abstract: Spinal muscular atrophy with respiratory distress (SMARD1) is an autosomal recessive neuromuscular disease caused by mutations in the IGHMBP2 gene, encoding the immunoglobulin μ‐binding protein 2, leading to motor neuron degeneration. It is a rare and fatal disease with an early onset in infancy in the majority of the cases. The main clinical features are muscular atrophy and diaphragmatic palsy, which requires prompt and permanent supportive ventilation. The human disease is recapitulated in the neuromuscular degeneration ( nmd ) mouse. No effective treatment is available yet, but novel therapeutical approaches tested on the nmd mouse, such as the use of neurotrophic factors and stem cell therapy, have shown positive effects. Gene therapy demonstrated effectiveness in SMA, being now at the stage of clinical trial in patients and therefore representing a possible treatment for SMARD1 as well. The significant advancement in understanding of both SMARD1 clinical spectrum and molecular mechanisms makes ground for a rapid translation of pre‐clinical therapeutic strategies in humans.